Trunk stabilization, body balance, body perception, and quality of life in professional physically disabled and able-bodied archers - Arkin, I.; Budak, M. (Sport Sciences for Health, 2021)
Background Archery is defined as a static sport that requires postural control, upper body strength and balance ability to achieve high scores.